Ein Spiel mit Stereotypen? Zu Matthias Nawrats Roman Die vielen Tode unseres Opas Jurek (2015) - Drynda, Joanna (Studia Germanica Posnaniensia, 2017)
Matthias Nawrat, born in 1979 in Opole, has been living in Germany since 1989. In his latest novel Die vielen Tode unseres Opas Jurek (2015) the author returns to the country of his birth in order to recount one century of the Polish as well as of the Polish-German history. The ghastly-comical family-story uses mobile parts of stage scenery from a picaresque novel – in the centre stands a man (grandfather Jurek) who, in spite of all the atrocities of the 20th century, won’t let others prevent him from leading a joyful life. While staging the story of a struggling artist, he refers back to stereotypes, obviously with the intention of strenghtening the existing models. This contribution poses a question if the game has been successful.